Ergonomics and health aspects of work with computers international conference, EHAWC 2011, held as part of HCI international 2011, Orlando, FL, USA, July 9-14, 2011. proceedings - EHAWC 2011 (2011 Orlando, Fla.); Robertson, Michelle M.; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the International Conference on Ergonomics and Health Aspects of Work with Computers, EHAWC 2011, held within the framework of the 14th International Conference on Human-Computer Interaction, HCII 2011, incorporating 12 thematically similar conferences. A total of 4039 contributions was submitted to HCII 2011, of which 1318 papers were accepted for publication. The 25 papers presented in this volume were carefully reviewed and selected for inclusion in the book. They are organized in topical sections on quality of working life; health and well-being; and interactive devices and interfaces.
Electronic reproduction.
Keywords: Human engineering -- Congresses; Medical records -- Data processing; Optical pattern recognition; Social sciences -- Data processing; Information Systems; Electronic books